Ageing in a consumer society from passive to active consumption in Britain - Jones, Ian Rees (Policy Press, 2008)
A timely and critical review and analysis of the development and implementation of New Labour's rural policies since 1997
Title from publisher's bibliographic system (viewed on 13 Jan 2022)
Keywords: Older consumers / Great Britain; Older people / Great Britain / Social conditions; Consumption (Economics) / Great Britain; Older consumers / Great Britain / Attitudes; Älterer Mensch; Verbraucherverhalten; Großbritannien; Statistik -- 1960-2008